INFLUENCIA DEL PERIODISMO AMBIENTAL EN LA CALIDAD DE VIDA DE LAS MUJERES DEL RECINTO AGUAS CLARAS. - Sanmartin Panezo, Wendy Juleidy (2022)
Environmental journalism deals with information related to the environment and everything that is linked to the impacts and modifications to the natural environment, also in obtaining and treating written, oral, audiovisual information, based on environmental issues. As well as the scientific, social, political, economic, cultural, environmental, and ethical aspects thereof. Currently there are not many journalists in the canton who carry out Environmental Journalism, but the few that exist seek a space in some local media outlet to be able to inform citizens, and give advice on how to care for and preserve a healthy environment for future generations. This research will benefit the women of the Aguas Claras campus in the Canton of Valencia, an action through which a greater acceptance of care for the environment will be achieved through workshops, with the response being conservation and a great increase in the care and hygiene of the environment. sector, as an advance in caring for the environment.